DESAIN KARTU QRTET PADA MATERI TUMBUHAN UNTUK OPTIMALISASI KEEFEKTIFAN PEMBELAJARAN BERDIFERENSIASI PADA PESERTA DIDIK SEKOLAH DASAR - Zulfah Tahta Alfina; Sudarmin; Sri Wardani; Ani Rusilowati; Bambang Subali; Wahyu Lestari (STKIP Subang, 2024)
Merdeka Curriculum is designed as a more flexible curriculum framework that focuses on developing learners' character and skills. The selection of learning content and media according to learners' learning styles often raises issues of perceived injustice and conflict. The purpose of this article is to find learning content and media that can increase the efficiency of the teaching and learning process and reduce envy among learners regarding the choice of material. The Plant QRtet Card is a learning media that combines a quartet card game and augmented reality (AR) technology. This article offers a solution to providing differentiated learning content that can accommodate the diverse needs of learners based on their learning styles. By differentiating learning, learners will be more engaged, motivated, and able to develop their maximum potential. Hopefully, the Plant QRtet Card can optimize the effectiveness of differentiated learning to achieve maximum learning outcomes.